PEMBERIAN KOMBINASI COKELAT KAYU MANIS EFEKTIF UNTUK MENURUNKAN NYERI DISMENOREA PRIMER - Yudrika, Filza; Rahayu, Sri; Supriyadi, Supriyadi (Poltekkes Kemenkes Bandung, 2025)
Menstruation is a monthly occurrence during the reproductive period which sometimes causes discomfort called dysmenorrhea. Dark chocolate and cinnamon are known to have good analgesic properties. Many efforts have been made to provide dark chocolate and extra cinnamon to reduce dysmenorrhea. However, the combination of the two has never been done, researchers have developed an innovative cinnamon chocolate product to reduce dysmenorrhea in adolescent girls. Objective to determine the effect of cinnamon chocolate, prostaglandin levels and the degree of menstrual pain in adolescent girls. True-experiment research with pretest posttest control group design. Study population of adolescent girls at SMPN 3 Kota Sungai Penuh. The total population is all female adolescent students with a total sample of 40 respondents divided into 2 groups. Intervention group was consuming cinnamon chocolate 40 g/day with 5 mg cinnamon content for 3 days. Bivariate analysis using Wilcoxon and Man Whitney. Dysmenorrhea pain scores before and after in the intervention group were 7.25 and 2.30, in the control group were 6.85 and 4.90, and there was a significant effect of giving cinnamon chocolate on reducing dysmenorrhea pain (p=0.000). The prostaglandin level scores before and after in the intervention group were 1.377.05 and 499.39, in the control group were 1,260.71 and 909.42, and there was a significant decrease in prostaglandin hormones (p=0.000). Consuming 40 grams of cinnamon chocolate/day for 3 days has a significant effect on reducing dysmenorrhea pain and prostaglandin hormone levels in adolescent girls.